2022
DOI: 10.7759/cureus.30493
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diffusion-Weighted Magnetic Resonance Imaging in Differentiating Benign From Malignant Thyroid Nodules: A Descriptive Observational Study

Abstract: BackgroundCurrently, no effective and reproducible imaging method can quantitatively differentiate between benign and malignant thyroid nodules. This study aimed to assess the role of diffusion-weighted imaging (DWI) in differentiating benign from malignant thyroid nodules. MethodologyWe conducted an observational study in the Department of Radiodiagnosis at R. L. Jalappa Hospital and Research Center, Kolar, India. The study was conducted from January 2020 to June 2021, among 43 patients with thyroid swelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Wildman Tobriner et al [22] showed that an arti cial intelligenceoptimized TI-RADS can moderately improve speci city and sensitivity compared to TI-RADS. In recent years, there has been a gradual increase in the research of MRI for diagnosing both benign and malignant thyroid nodules [23][24][25][26][27] and predicting the preoperative aggressiveness of papillary thyroid carcinoma [28-34],…”
Section: Discussionmentioning
confidence: 99%
“…Wildman Tobriner et al [22] showed that an arti cial intelligenceoptimized TI-RADS can moderately improve speci city and sensitivity compared to TI-RADS. In recent years, there has been a gradual increase in the research of MRI for diagnosing both benign and malignant thyroid nodules [23][24][25][26][27] and predicting the preoperative aggressiveness of papillary thyroid carcinoma [28-34],…”
Section: Discussionmentioning
confidence: 99%